Biology of snakes of the genus Tretanorhinus: an integrative review - Barquero Arroyo, Marco David (2019)
Many aspects of the biology of various snake species remain unknown, and the extent of this lack of information is not always clear. As new research usually depends upon previous findings, the gaps in our knowledge and the accuracy of published information are of major importance. Therefore, an analysis of all available information on snakes of the genus Tretanorhinus, from both the literature and museum specimens, is presented here to illuminate existing knowledge gaps. The database compiled from 87 documents referring to snakes of this genus and 755 specimens held in scientific collections revealed major gaps and contradictory information for all four species of this genus. Data on morphology, ecology, and natural history are completely absent for T. mocquardi and T. taeniatus, whereas confusing distribution reports exist for T. nigroluteus. The potential consequences of these problems were determined, and some suggestions for correcting them are addressed. Specifically, we consider that focused efforts on the validation of current species and subspecies, field and lab studies of ecology and behavior, and estimations of population dynamics, are necessary.